El impacto de los factores de salud pública, socioeconómicos y ambientales en las tasas de infección y mortalidad por SARS-CoV-2 en Perú: explorando el papel de la obesidad - Samillan Soto, Victor Jesús; VELAZCO, Yessenia K; ROJAS, Eduardo; QUIROZ CORNEJO, Karen V; QUISPE VILLANUEVA, Manuel S; CHAMOCHUMBI, Miguel Jaime; ARELLANO SALAZAR, Martha; ZUTTA, Brian R (Nutrición Clínica y Dietética Hospitalaria, 2023)
Objective. To explore the impact of public health, socio-economic and environmental factors on the rate of infection and mortality of SARS-CoV-2 on gender and age groups in Peru. Methods. We explored the relationships, using Pearson’s correlation and stepwise linear regression, between the infection and mortality cases per 100,000 individuals with public health data (obesity prevalence, total number of health infrastructure, hypertension prevalence, active smokers, tuberculosis cases), socio-economic data (health needs not met, childhood malnutrition, access to potable water, access to chlorinated water system) and environmental data (NO2 concentration) in Peru. We used confirmed cases from the 26 department level jurisdictions from 2020, before known variants were registered within the country and focused on gender and age groups, as well as case-fatality rate. Results. Multiple linear regression models indicate obesity, air quality, access to chlorinated water system, and prevalence of smoking are influential factors in the distribution of infection and mortality for middle-age and elderly female and male groups, but prevalence of TB and health needs not met were more important for children and young adults in Peru. Case-fatality rate was weakly associated with NO2 concentration. Conclusions. Obesity, exposure to poor air quality, and socio-economic conditions are significant factors in the morality of individuals above the age of 40 for both men and women, while other health factors appear to be more important to those younger than 40. The combination of these factors played a significant role during the first wave of SARS-CoV-2 infection in Peru in 2020.